Analysis of the Volatile Constituents of Rabdosia rubescens by Gas Chromatography- Mass Spectrometry Using Headspace Solid-Phase Micro-Extraction - Wu, Ye-Ping; Dong, Liang; Yuan, Ke (Asian Journal of Chemistry, 2010)
The extraction of chemical constituents of volatile oil from Rabdosia rubescens by the technique of headspace solid-phase micro-extraction (HS-SPME) is reported. The chemical constituents of volatile oils separated were identified by gas chromatography-mass spectrometry analysis. The relative percentage content of chemical constituents of volatile oil were determined by area normalization method. Chromatographic conditions: HP-5 elastic quartz capillary-tube chromatographic column (30 m × 0.25 mm, 0. 25 mm); temperature-increasing procedure: keep the initial temperature 45 ºC for 2 min and then increase the temperature to 250 ºC and keep it for 0.5 h at the rate of 10 ºC min-1. The temperature at the sample-feeding entrance is 250 ºC and the flowing rate is 0.8 mL min-1 without any divided sample-feeding. By the method of solid-phase micro-extraction, we identified 60 kinds of constituents, the identified part occupies 98.27 % of the total volatile oil and its main chemical constituents are the compounds of hydrocarbon, alcoholate and ketone. Compared with the traditional steam distillation method, the technique of headspace solid-phase micro-extraction has the advantages of short extracting time, small sample amount and no need of extracting the solution. This experiment result enhances present understanding of chemical constituents of volatile oils in Rabdosia rubescens and provides further reference for the development and utilization of the natural medicinal resource.